The effect of Nb and heat treatment on the corrosion behavior of ferritic stainless steel in acid environments - Demiroren, H.; Aksoy, M.; Erbil, M. (Consultants Bureau/Springer, 2008)
The corrosion properties of ferritic stainless steel with admixtures of 0.5, 1.0, and 3.0 wt.% Nb are studied in 0.1M H(2)SO(4) and 0.3M HCl solutions. The results obtained by the impedance and mass-loss methods demonstrate that the procedure of alloying with niobium and diffusion treatment positively affect the corrosion resistance of steel in these solutions.
Keywords: Microstructure